Broadband 4-way power divider with 45° phase differences between output ports. Issue 18 (December 2017) - Hayashi, Hitoshi; Nakayama, Youichi; Mizusawa, Junichi
Abstract: This paper presents broadband 4-way power divider with 45° phase differences between output ports. The divider is developed by combining a broadband 45° power divider and 90° power dividers, and is implemented on a 4-layer FR4 substrates, by using inner-layer crossovers, instead of conventional bonded crossovers. Over the frequency range from 400 to 700 MHz, the fabricated power divider exhibits power splits of − 6.8 ± 0.9 dB and return losses of greater than 14 dB Furthermore, isolation between the output ports is greater than 16 dB, and the phase differences between output ports are within 5° of the desired values (90°, −45°, and −135°).